Perlindungan Hukum Pidana Terhadap Transaksi Yang Mempunyai Tujuan Pembayaran Menggunakan Mata Uang Rupiah Di Indonesia - Rafika, Aliya tur; Iriyanto, Echwan; Nugroho, Fiska Maulidian (Journal of Economic and Business Law Review, 2022)
Abstract Transactions that have the purpose of payment in the territory of Indonesia use the rupiah currency as stipulated in Law no. 7 of 2011 concerning Currency. However, the "Mualamah Market" uses dinar and dirham payment transactions, and Indonesia's border areas with Malaysia, Singapore and Timor Leste are very vulnerable to using Ringgit, Singapore Dollars and US Dollars as well as lawyers being paid using foreign currencies and there are still many cases other. The purpose of this study is to determine the form of criminal threats that can provide a deterrent effect on perpetrators and can scare the general public so that all people in the territory of Indonesia use the rupiah currency in transactions that have a payment purpose. The methodology used is normative juridical by using a statutory, conceptual, historical and comparative approach with the support of the theory of punishment and legal certainty or the principle of legality, as well as the principle of territoriality. The results of this study indicate that every transaction that has the purpose of payment in the territory of Indonesia is required to use the rupiah currency. 7 of 2011 concerning Currency. The criminal threat in Article 33 paragraph (1) of Law no. 7 of 2011 concerning Currency is not in accordance with the theory of punishment (combined theory) because the sanctions are too light, both fines and physical crimes so that the sanctions are not yet effective to provide a deterrent effect or frighten the general public. Keywords: Criminal Law Protection, Payment Transactions, and Rupiah